Supercooling points of diapausing forest tent caterpillar (Lepidoptera: Lasiocampidae) eggs. Issue 5 (11th March 2016) - Uelmen, Johnny A.; Duman, John G.; Lindroth, Richard L.; Schwartzberg, Ezra G.; Raffa, Kenneth F.
Abstract: Forest tent caterpillar ( Malacosoma disstria Hübner; Lepidoptera: Lasiocampidae) is a widely distributed defoliator that undergoes intermittent outbreaks. It overwinters as pharate larvae within egg bands, is univoltine, and experiences low winter temperatures in its northern range. Little is known about how low temperatures affect winter survival and cold tolerances, their cold tolerance strategy, or how cold tolerances may vary over time and among populations. We evaluated supercooling points (SCPs) from four populations of M. disstria eggs collected along a 552 km latitudinal gradient from southern Wisconsin to northern Minnesota, United States of America. To test for potential effects of winter environment, we also administered three overwintering regimes (Madison, Wisconsin; Cloquet, Minnesota; Ely, Minnesota). Supercooling points were recorded in November, February, and March of 2011–2012. Supercooling points varied with maternal source (egg band), time of winter season, population source, and overwintering treatment. Means ranged from −26.8 °C (±0.5 °C) to −40.3 °C (±0.3 °C), accordingly. In a separate laboratory experiment, 89% of pharate larvae held at −20 °C (18.3 °C above coolest mean SCP) survived, but none held at −45 °C (6.7 °C below lowest mean SCP) survived. This relatively high degree of cold tolerance in its overwintering stage, due to freeze avoidance, may partially explain survival patterns and limits of overwintering M. disstria in northern populations.